Laparoscopic versus open unisegmentectomy in two specialized centers. Feasibility and short-term results. Issue 5 (May 2020) - Garbarino, Giovanni M.; Marchese, Ugo; Tobome, Romaric; Ward, Marc A.; Vibert, Eric; Gayet, Brice; Cherqui, Daniel; Fuks, David
Abstract: Background: Anatomical segmentectomy is defined as the complete removal of the Couinaud's segment. The aim of this study was to compare the perioperative outcomes of laparoscopic (LS) versus open (OS) unisegmentectomy in two high volume centers. Methods: A retrospective review of all consecutive unisegmentectomies from 2007 to 2017 was performed at the Institut Mutualiste Montsouris and at the Hepatobiliary Center of Paul Brousse Hospital. Results: A total of 177 patients underwent unisegmentectomy: 58 LS vs 52 OS in the anterolateral segments, 33 LS vs 34 OS in the posterosuperior segments. HCC were more frequent in the OS group, whereas colorectal liver metastases were more frequently treated with LS. Blood loss (200 vs. 400 ml, p = 0.006), operative time (238 vs. 267 min, p = 0.048) and median length of stay (6 vs. 8 days, p = 0.036) were significantly lower in the LS group. The resection margins (4 mm vs. 2 mm, p = 0.763) and the overall morbidity did not differ between the two groups. In the posterosuperior segment, OS group had more pulmonary complications (9 vs. 29%, p = 0.035). Conclusion: Laparoscopic anatomical unisegmentectomies for selected patients, even with postero-superior based tumors, in specialized centers seems to be safe and feasible.